Direct transfer of wafer-scale graphene films. (22nd June 2017) - Kim, Maria; Shah, Ali; Li, Changfeng; Mustonen, Petri; Susoma, Jannatul; Manoocheri, Farshid; Riikonen, Juha; Lipsanen, Harri
Abstract: Flexible electronics serve as the ubiquitous platform for the next-generation life science, environmental monitoring, display, and energy conversion applications. Outstanding multi-functional mechanical, thermal, electrical, and chemical properties of graphene combined with transparency and flexibility solidifies it as ideal for these applications. Although chemical vapor deposition (CVD) enables cost-effective fabrication of high-quality large-area graphene films, one critical bottleneck is an efficient and reproducible transfer of graphene to flexible substrates. We explore and describe a direct transfer method of 6-inch monolayer CVD graphene onto transparent and flexible substrate based on direct vapor phase deposition of conformal parylene on as-grown graphene/copper (Cu) film. The method is straightforward, scalable, cost-effective and reproducible. The transferred film showed high uniformity, lack of mechanical defects and sheet resistance for doped graphene as low as 18 Ω/sq and 96.5% transparency at 550 nm while withstanding high strain. To underline that the introduced technique is capable of delivering graphene films for next-generation flexible applications we demonstrate a wearable capacitive controller, a heater, and a self-powered triboelectric sensor.